(In-)Visible Living Space as the Educational Space Dreams-Self-Narration in Biographies of Elderly People - Piasecka, Malgorzata (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The objective of the paper is providing an answer to the question about educational and causative dimensions of dreams-self-narrations in biography of senior individuals. In the theoretical part, the authoress focuses on analyses concerning respectively: (in-)visible living space, trajectory of individual biographies and characteristics of dreams as self-narrations in structuring one’s own biography. In the methodological part, the authoress presents the assumptions of a research project based on the biographical method by applying narrative interviews. In the empirical part, results of vertical and horizontal analyses are presented in the form of the worked out biographical profiles in the context of highlighted areas of study.